كفالة اليتيم في التشريع الجزائري - زغيشي, سعاد (University of Eloued جامعة الوادي, 2017)
الكفالة نظام بديل عن التبني شرعا وقانونا سواء لمعلومي النسب أو مجهوليه حفظا للأنساب وعدم اختلاطها تضمن للطفل المتكفل به الحماية في ظل أسرة بديلة ليتم إدماجه في المجتمع حتى لا يكون عرضة للانحراف والإجرام. Abstract: The guarantee is an alternative system for adoption in Islamic law and positive law, both for persons of known or unknown descent , in order to preserve the genealogy. The guarantees the child who is protected by an alternative family to be integrated into society so as not to be subject to delinquency and criminality
orphan's guarantee in Algerian legislation
مجلة البحوث والدراسات المجلد 14 العدد 02 جامعة الوادي
Keywords: اليتيم- الكفالة- القانون; orphan - guarantee - law